2006
DOI: 10.1097/01.blo.0000188557.65387.fc
|View full text |Cite
|
Sign up to set email alerts
|

Does Screw Configuration Affect Subtrochanteric Fracture after Femoral Neck Fixation?

Abstract: A subtrochanteric femur fracture after cannulated screw fixation of a femoral neck fracture is a devastating complication. We hypothesized that an apex-distal screw orientation would tolerate higher loads to subtrochanteric fracture. Human cadaveric femora were instrumented with three cannulated screws in either an apex-distal or an apex-proximal configuration. Specimens were loaded along the mechanical axis to failure creating a subtrochanteric femur fracture. Ultimate load to failure and the effect of bone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 18 publications
3
30
0
3
Order By: Relevance
“…This puts great demand to both the design of the implant's anchor and to the local bone quality. Regarding fixation with three screws, experimental studies have shown increased mechanical stability using a triangular pattern compared to a vertical screw orientation and that the apex down configuration reduces the risk of a later subtrochanteric fracture compared to apex up configuration (Selvan et al 2004, Oakey et al 2006, Lichtblau et al 2008. A recent clinical report including 202 patients treated for a femoral neck fracture with either a triangle screw configuration or an inverted triangle configuration, found a significant difference in union rate in favor of the inverted triangle configuration (Yang et al 2013).…”
Section: Multiple Pins and Screwsmentioning
confidence: 99%
See 1 more Smart Citation
“…This puts great demand to both the design of the implant's anchor and to the local bone quality. Regarding fixation with three screws, experimental studies have shown increased mechanical stability using a triangular pattern compared to a vertical screw orientation and that the apex down configuration reduces the risk of a later subtrochanteric fracture compared to apex up configuration (Selvan et al 2004, Oakey et al 2006, Lichtblau et al 2008. A recent clinical report including 202 patients treated for a femoral neck fracture with either a triangle screw configuration or an inverted triangle configuration, found a significant difference in union rate in favor of the inverted triangle configuration (Yang et al 2013).…”
Section: Multiple Pins and Screwsmentioning
confidence: 99%
“…Some research groups prefer to keep the diaphysis in a neutral position without adduction, abduction, flexion or extension (Brandt et al 2010). Others again use a calculated mechanical axis for each single femur (Oakey et al 2006). A distal anchorage that allows angulations and rotations of the femurs opens the possibility of simulating abductor muscles and the iliotibial tract.…”
Section: Test Setupsmentioning
confidence: 99%
“…Typically, three cancellous lag screws oriented along the femoral neck axis and parallel to each other are placed in an inverted triangle. This configuration is biomechanically superior to any other orientation and decreases the risk of subtrochanteric fracture [36][37][38][39][40][41][42][43]. As demonstrated by Lindequist et al [44••] and other previous authors, the first screw should be placed within 3 mm of the cortical calcar femorale to allow a three-point buttressing effect (with fixation in the dense subcortical femoral head, the calcar, and the lateral femoral cortex of entry) [45].…”
Section: Implant Choicementioning
confidence: 99%
“…7,9 The anatomy of the proximal humerus is similar to that of the proximal femur to a certain extent. Theoretically, a parallel pin construct should have a better mechanical advantage than the convergent pin construct.…”
Section: Discussionmentioning
confidence: 98%